Less strength and more fractures for MGUS bones - Terpos, E.; Dimopoulos, M.A. (Blood, 2014)
In this issue of Blood, Farr et al showed that patients with monoclonal gammopathy of undetermined significance (MGUS) have increased cortical bone porosity and reduced bone strength,1 conditions that can lead to the increased fracture risk, which has been reported in MGUS patients. © 2014 by The American Society of Hematology.